The Dynamically Changing Publication Universe as a Reference Point in National Impact Evaluation: A Counterfactual Case Study on the Chinese Publication Growth - Stahlschmidt, Stephan; Hinze, Sybille (Frontiers in Research Metrics and Analytics, 2018)
National bibliometric performance is commonly measured via relative impact indicators which appraise absolute national values through a global environment. Consequently the resulting impact values mirror changes in the national performance as well as in its embedding. In order to assess the importance of the environment in this ratio, we analyse the increase in Chinese publications as an example for a structural change altering the publication universe. Via a counterfactual comparison we observe how Chinese publications differ in their citation-based relevance attribution by benefiting especially Asian countries, while scientifically leading countries in the West gain less than postulated by the former status quo. Due to the substantial quantity of Chinese publications this differentiation in relevance attribution imposes globally noticeable effects on national impact statistics. We argue that such structural changes in the environment have to be taken into account for an unbiased measurement of national bibliometric performance.